2011
DOI: 10.1097/jgp.0b013e318202fc8a
|View full text |Cite
|
Sign up to set email alerts
|

The Vascular Depression Hypothesis: An Update

Abstract: Since being proposed as a unique subtype of late-life depression (LLD), the vascular depression hypothesis has received considerable research attention. Although this effort has generated considerable empirical support for the validity of the subtype, fundamental questions remain including how the illness is defined, whether cerebrovascular disease and executive dysfunction (ED) define two separate entities or one underlying subtype, and whether ED is responsible for poor response to antidepressant treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
70
0
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 50 publications
5
70
0
10
Order By: Relevance
“…Thus, there is still a prominent lack of epidemiologic data on depression unilateral following post-stroke.Considering the aim to verify whether there is an influence of post-RHD depression in eight cognitive functions, in a general perspective RHD+ adults presented cognitive changes in at least one subtest in all neuropsychological domains assessed. These findings corroborate the literature which investigates the relationship between post-stroke depression and cognitive performance, even when they do not consider the isolated contribution of each cerebral hemisphere in the execution of the tasks adopted (12) . Despite of the fact that this has not been the main aim of Barker-Collo's (23) study, for instance, RHD patients with a diagnosis of depression presented lower performance in late recall in semantic-verbal memory.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Thus, there is still a prominent lack of epidemiologic data on depression unilateral following post-stroke.Considering the aim to verify whether there is an influence of post-RHD depression in eight cognitive functions, in a general perspective RHD+ adults presented cognitive changes in at least one subtest in all neuropsychological domains assessed. These findings corroborate the literature which investigates the relationship between post-stroke depression and cognitive performance, even when they do not consider the isolated contribution of each cerebral hemisphere in the execution of the tasks adopted (12) . Despite of the fact that this has not been the main aim of Barker-Collo's (23) study, for instance, RHD patients with a diagnosis of depression presented lower performance in late recall in semantic-verbal memory.…”
Section: Discussionsupporting
confidence: 81%
“…Among those studies, the research conducted by Alexopoulos (11) , for instance, emphasizes that lesions in the frontolimbic and frontoestriatic networks are associated withwith executive functions deficits; however, the contributions of each hemisphere are not considered in this process. According to Sneed and Culang-Reinlieb (12) , post-stroke depression is also associated withwith executive dysfunction, although independently of lesion type. Brodaty et al (13) identified that apathy following stroke is linked to low performance in tasks measuring concentrated attention, working memory and processing speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large cohort of 157,243 Danish patients with stroke, diabetes was found as a risk factor for PSD 34 . The findings of an association between the occurrence of a depressive syndrome in the elderly population and the presence of white matter lesions of vascular origin, particularly in the frontal regions, have led to the hypothesis of the existence of a "vascular depression", which would be linked to microangiopathy 35 . Based on that, one could speculate whether patients with diabetes are more susceptible to the development of depressive symptoms after a major vascular insult superimposed on chronic vascular microlesions.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that also a high rate of depression in patients, who have had a stroke, demonstrated also White Matter Hyperintensities (WMIs). The notable infrequent family history of mood disorders in depression occurring in the context of silent stroke should be mentioned (Sneed & Culang-Reinlieb, 2011).…”
mentioning
confidence: 99%